'GRINDING THE TEXTURES OF HARMONY': HEROIC DIFFICULTY IN GEOFFREY HILL'S CLAVICS. (2nd December 2014) - Hawlin, Stefan
Abstract : Appreciation of Geoffrey Hill's The Daybooks has been slow. In relation to Clavics (2011), the fourth 'Daybook', the issue of Hill's 'difficulty' has again come to the fore in responses. Actually, the so-called difficulty may have less to do with stylistic features or allusion than with questions concerning Hill's arguments and his Christian humanism. This essay sets up a Gradus ad Parnassum of 'difficulty', moving from a relatively easy poem to one at the highest level of challenge. It looks at Hill's engagement with seventeenth-century music and religious faith, which he focuses on his view of the royal composer William Lawes (1602–45), who he sees as a heroic figure struggling to fulfil the true mission of the artist amid the ill-temper and chaos of his times: the 'world in its rot'. The conclusion here is that Clavics is not some ne plus ultra of difficulty, but a boldly original lyric sequence, interrogating the true role of the artist, and other figures, in relation to the discords of national history.